Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T16:06:22+01:00
A)
3(2-3)+3=2(3-3)
6-9+3=6-6
0=0

liczba 3 jest rozwiązaniem tego równania.

b)
2+5(3-1)=3(9+5*3)
2+15-5=27+45
15=72


liczba 3 nie jest rozwiązaniem tego równania.

c)
2(3*3-1)+3=10-3(5-2*3)
18-2+3=10-15+18
18-5=-5+18
13=-13


liczba 3 nie jest rozwiązaniem tego równania.


licze że pomogłam, i licze na maxa
pozdrawiam.!
1 1 1
2010-03-06T16:15:39+01:00
A) 3(2-x)+x=2(3-x)
3(2-3)+3=2(3-3)
3(-1)+3=2(0)
-3 +3= 0
0=0
b) 2+5(x-1)=3(9+5x)
2+5(3-1)=3(9+5×3)
2+5×2=3×24
2+10=72
12≠72
c) 2(3x-1)+x=10-3(5-2x)
2(3×3-1)+3=10-3(5-2×3)
2×8+3=10-3(-1)
16+3=10+3
19≠13